2021
DOI: 10.1002/bmb.21519
|View full text |Cite
|
Sign up to set email alerts
|

Introducing SELEX via a semester‐long course‐based undergraduate research experience (CURE)

Abstract: With the growing importance of the field of RNA biology, undergraduates need to perform RNA-related research. Systematic evolution of ligands by exponential enrichment (SELEX) has become an important method in RNA biology. The principles of SELEX were applied to a semester-long course-based undergraduate research experience (CURE) in which two rounds of in vivo functional selection of regions of a viral RNA were performed. As the labwork had an unknown outcome, students indicated that they were excited by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Unlike apprenticeship research experiences conducted in a lab with limited participants, CUREs are designed for large classes as core learning activities that allow as many students as possible to be exposed to scientific research experiences . Studies have demonstrated that the CUREs positively affect students’ self-efficacy, self-determination, and problem-solving abilities as well as build their confidence in lab abilities . In addition, early engagement of undergraduates in CUREs has positive effects on graduation rates and the completion of science degrees .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike apprenticeship research experiences conducted in a lab with limited participants, CUREs are designed for large classes as core learning activities that allow as many students as possible to be exposed to scientific research experiences . Studies have demonstrated that the CUREs positively affect students’ self-efficacy, self-determination, and problem-solving abilities as well as build their confidence in lab abilities . In addition, early engagement of undergraduates in CUREs has positive effects on graduation rates and the completion of science degrees .…”
Section: Resultsmentioning
confidence: 99%
“…5 Studies have demonstrated that the CUREs positively affect students' self-efficacy, self-determination, and problem-solving abilities 71 as well as build their confidence in lab abilities. 85 In addition, early engagement of undergraduates in CUREs has positive effects on graduation rates and the completion of science degrees. 86 Therefore, the CUREs may represent a promising solution for the improved learning outcomes of undergraduate biochemistry courses, although several obstacles, including faulty competency, equipment, and techni-ques, need to be carefully evaluated when applying CUREs in undergraduate institutions.…”
Section: Rank Referencementioning
confidence: 99%